A Content Analysis of Reddit Users' Posts about Challenges to Contraceptive care-seeking during COVID-19-related Restrictions in the United States. Issue 10 (3rd October 2022) - Pleasure, Zoe H.; Frohwirth, Lori F.; Li, Naomi; Polis, Chelsea B.
ABSTRACT: The COVID-19 pandemic in the United States caused disruptions in care seeking and delivery during the spring of 2020, including for contraceptive care. We examined how some individuals experienced and responded to barriers to accessing contraceptive care by conducting a content analysis of relevant Reddit posts. We collected 2666 posts by scraping relevant subreddits from February 1, 2020, to April 15, 2020, and filtering by selected keywords. Among the 101 posts on contraception and the COVID-19 pandemic, we explored three main themes: barriers to accessing general healthcare during the early pandemic, problems and concerns specific to contraceptive use, and attempts to navigate the obstacles to contraceptive care or use-related concerns. The Reddit posts demonstrated the disruptive force the early pandemic had on contraceptive care and provided a unique window into the concerns posters expressed on Reddit during this time. Many posters asked questions related to accessing contraception and side effects and sought reassurance from these online forums. Our results suggest that there were barriers to accessing reliable, high-quality, and evidence-based information about contraception during this disruption in care. The findings also underscore that conversational and interactive means of seeking out information are important modes for learning about and discussing contraception for some and may be especially helpful during clinic closures and other restrictions on access.